(untitled) (Veterinary Science, 2023)
The objective of this work is to present the use of a synthetic ligament for the repair of chronic rupture of the Achilles tendon. A case of a large mixed breed adult canine with plantigrade support of the right hind limb is presented. After performing a detailed physical examination of the area, correlating with anamnesis and taking radiographic plates to rule out bone involvement in the lesion, the diagnosis of Achilles tendon rupture was reached. It was decided to establish surgical treatment using a biocompatible synthetic ligament together with an external fixation system to restore the functionality of the limb.